2020
DOI: 10.1111/ina.12748
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on sleep quality affected by carbon dioxide concentration

Abstract: This study comprehensively investigated the impact of indoor carbon dioxide (CO2) concentration on sleep quality. Three experimental conditions (800, 1900, 3000 ppm) were created in chambers decorated as bedroom and other environmental parameters that may influence the sleep quality were under strict control. Sleep quality of 12 subjects (6 men and 6 women) was monitored for 54 consecutive days through sleep quality questionnaire and physiological measures. Both subjective and physiological results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 49 publications
(75 reference statements)
1
18
3
Order By: Relevance
“…4 A recent study measured the sleep quality of young adults with polysomnography (PSG) at different CO 2 levels; the duration of deep sleep was found to decrease at higher CO 2 levels. 6 However, the CO 2 levels in this experiment were higher than have been observed in most field surveys. 5 To the best of our knowledge, no reports on the effects of bedroom ventilation on elderly subjects are available.…”
Section: Introductioncontrasting
confidence: 60%
See 1 more Smart Citation
“…4 A recent study measured the sleep quality of young adults with polysomnography (PSG) at different CO 2 levels; the duration of deep sleep was found to decrease at higher CO 2 levels. 6 However, the CO 2 levels in this experiment were higher than have been observed in most field surveys. 5 To the best of our knowledge, no reports on the effects of bedroom ventilation on elderly subjects are available.…”
Section: Introductioncontrasting
confidence: 60%
“…The threshold of 1150 ppm was proposed based on Mishra et al’s study 4 . A recent study measured the sleep quality of young adults with polysomnography (PSG) at different CO 2 levels; the duration of deep sleep was found to decrease at higher CO 2 levels 6 . However, the CO 2 levels in this experiment were higher than have been observed in most field surveys 5 .…”
Section: Introductionmentioning
confidence: 70%
“…Where CER in L/h, VR in m 3 /h, C Steady : time‐average CO 2 concentration at the steady‐state period in ppm, C a : ambient CO 2 concentration in ppm under the period of steady state.…”
Section: Methodsmentioning
confidence: 99%
“…In the absence of other markers, its concentration indoors is frequently used as an indicator of the ventilation rate (VR) (when occupants are present) 2 and the degree of air mixing (ventilation efficiency) as well as indoor air quality (IAQ). Poor IAQ as indicated by a high CO 2 concentration has been shown to affect sleep quality and consequently next‐day work performance 3–5 . An increasing number of studies link bedroom ventilation to sleep quality 3–7 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kajtar et al 12 reported that controlled human exposures to CO 2 between 2000 ppm and 5000 ppm, with ventilation rates unchanged, were positively associated with perception of wellbeing and performance on some reading tasks. More recently, a study by Xu et al 13 found that sleep quality was negatively affected by increasing concentrations of CO 2 up to 3000 ppm. Moreover, Mishra et al 14 showed that with lower CO 2 levels, the number of awakenings throughout the night tended to decrease.…”
Section: Introductionmentioning
confidence: 99%